Analisis Strategi Pengembangan Ketenagaan dan Sumber Daya Manusia Perguruan Tinggi Keagamaan Islam (PTKI) - Rahmawati; Ali Nurhadi (AL-FIKRAH: Jurnal Studi Ilmu Pendidikan dan Keislaman, 2024)
Abstrak Relevansi manajemen ketenagaan dan sumber daya manusia dapat dilihat dari tenaga pendidik berperan sebagai ujung tombak atau kunci dari kualitas pembelajaran dan tenaga administrasi yang melakukan tugas dan tanggungjawabnya dengan baik dapat mendukung peningkatan mutu pendidikan. Tingkat profesionalitas ketenagaan bergantung pada kualitas manajemen sumber daya manusianya. Penyusunan strategi Menurut teori Jeffrey A Mello menganggap visi misi di Institusi sangat penting dijadikan sebagai tolak ukur dalam mengembangkan ketenagaan dan sumber daya manusia. Pengembangan rencana yang strategis disesuaikan dengan tahapan pertama analisis kebutuhan. Kemudian melakukan pelatihan dan pengembangan dengan inservive training berdasarkan tahapan pengelolaan ketenagaan. Lebih lanjut diperlukan evaluasi untuk mengukur peningkatan kemampuan ketenagaan dan SDM baik dari tenaga pendidik dan kependidikan yang berkualitas. Setelahnya sasaran mengenai target ketenagaan dan sumber daya manusia manjadi berkualitas sesuai dengan keahliannya. Terkahir orientasi, maka Institusi yang menaunginya akan meningkatan mutu karena ketenagaan dan SDM di dalamnya sudah berkualitas, hal ini juga termasuk pemimpin di PTKI sebagai top leader yang berkualifikasi dan bersifat kooperatif serta cepat menyesuaikan terhadap perubahan lingkungan. Kata kunci: Strategi, Pengembangan, Manajemen Ketenagaan dan Sumber Daya Manusia Abstract The relevance of manpower and human resource management can be seen from educators acting as the spearhead or key to the quality of learning and administrative personnel who perform their duties and responsibilities well can support the improvement of education quality. The level of professionalism of personnel depends on the quality of human resource management. According to Jeffrey A Mello's theory, the vision and mission in the institution is very important to be used as a benchmark in developing manpower and human resources. The development of a strategic plan is adjusted to the first stage of needs analysis. Then conduct training and development with inservive training based on the stages of energy management. Furthermore, an evaluation is needed to measure the improvement of the ability of personnel and human resources from both qualified educators and education. After that, the target regarding the target of manpower and human resources becomes quality in accordance with their expertise. Finally, the orientation, the institution that houses it will improve quality because the personnel and human resources in it are of high quality, this also includes leaders in PTKI as qualified and cooperative top leaders who quickly adapt to environmental changes. Furthermore, an evaluation is needed to measure the improvement of the ability of personnel and human resources from both qualified educators and education. After that, the target regarding the target of manpower and human resources becomes quality in accordance with their expertise. Finally, the orientation, the institution that houses it will improve quality because the personnel and human resources in it are of high quality, this also includes leaders in PTKI as qualified and cooperative top leaders who quickly adapt to environmental changes. Keywords: Strategy, Development, Manpower Management and Human Resources